2015
DOI: 10.3389/fnins.2015.00123
|View full text |Cite
|
Sign up to set email alerts
|

Influx mechanisms in the embryonic and adult rat choroid plexus: a transcriptome study

Abstract: The transcriptome of embryonic and adult rat lateral ventricular choroid plexus, using a combination of RNA-Sequencing and microarray data, was analyzed by functional groups of influx transporters, particularly solute carrier (SLC) transporters. RNA-Seq was performed at embryonic day (E) 15 and adult with additional data obtained at intermediate ages from microarray analysis. The largest represented functional group in the embryo was amino acid transporters (twelve) with expression levels 2–98 times greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 79 publications
(145 reference statements)
0
40
0
2
Order By: Relevance
“…; Saunders et al . ). Slc16a2 is a thyroid hormone transporter, which is expressed at similar levels in embryonic and adult choroid plexus; the others are all monocarboxylate transporters and expressed at a lower level in the rat embryonic plexus compared to the adult (Saunders et al .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Saunders et al . ). Slc16a2 is a thyroid hormone transporter, which is expressed at similar levels in embryonic and adult choroid plexus; the others are all monocarboxylate transporters and expressed at a lower level in the rat embryonic plexus compared to the adult (Saunders et al .…”
Section: Introductionmentioning
confidence: 97%
“…Slc16a2 is a thyroid hormone transporter, which is expressed at similar levels in embryonic and adult choroid plexus; the others are all monocarboxylate transporters and expressed at a lower level in the rat embryonic plexus compared to the adult (Saunders et al . ). Only Slc16a10 (MCT10) is expressed at a higher level in mouse and rat embryonic choroid plexus compared to adult (Liddelow et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, EPC migrating to cerebral microvessels in perinatal and early postnatal period appear in the microenvironment of excessive lactate and ketone bodies utilization. However, such proposal requires further assessment since recent transcriptome study has shown that MCT1 is expressed at lower levels in the embryonic choroid plexus (E15) than in the adult brain, whereas GLUT1 is expressed in an opposite manner (Saunders et al, 2013, 2015). …”
Section: Oxidative Metabolism Of Progenitor Endothelial Cells and Metmentioning
confidence: 99%